The healthy donor effect impacts self‐reported physical and mental health – results from the Danish Blood Donor Study (DBDS). (12th October 2017) - Rigas, A. S.; Skytthe, A.; Erikstrup, C.; Rostgaard, K.; Petersen, M. S.; Hjalgrim, H.; Ullum, H.; Kyvik, K. O.; Pedersen, O. B.
SUMMARY: Aims: This study aimed at quantifying the healthy donor effect by comparing self‐perceived mental and physical health between blood donors and non‐donors. Background: In theory, the selection process known as the healthy donor effect should result in better self‐perceived, health‐related quality of life in donors than in non‐donors. Methods: The Short Form‐12 data from the Danish Twin Registry (DTR) was compared with the data from the Danish Blood Donor Study (DBDS). Data on age, sex and smoking status were included in the analyses. The multivariable linear regression analysis was stratified by sex and age group intervals. Outcome variables were the mental component score (MCS) and the physical component score (PCS). Results: A total of 28 982 and 36 913 participants from the DTR and the DBDS, respectively, were included in this study. Younger donors had higher MCS than non‐donors, whereas MCS was only marginally high in older donors compared with non‐donors. In contrast, PCS was almost similar for both young donors and non‐donors. With the increase in age, non‐donors had lower PCS than donors. Conclusions: Two selection patterns were revealed. Among young individuals, better self‐perceived mental health was associated with a blood donor. With the increase in age, better self‐perceived physical health was associated with blood donation.